The Mouse Universal Genotyping Array: From Substrains to Subspecies. Issue 2 (1st February 2016) - Morgan, Andrew P; Fu, Chen-Ping; Kao, Chia-Yu; Welsh, Catherine E; Didion, John P; Yadgary, Liran; Hyacinth, Leeanna; Ferris, Martin T; Bell, Timothy A; Miller, Darla R; Giusti-Rodriguez, Paola; Nonneman, Randal J; et al.
Abstract: Genotyping microarrays are an important resource for genetic mapping, population genetics, and monitoring of the genetic integrity of laboratory stocks. We have developed the third generation of the Mouse Universal Genotyping Array (MUGA) series, GigaMUGA, a 143, 259-probe Illumina Infinium II array for the house mouse ( Mus musculus ). The bulk of the content of GigaMUGA is optimized for genetic mapping in the Collaborative Cross and Diversity Outbred populations, and for substrain-level identification of laboratory mice. In addition to 141, 090 single nucleotide polymorphism probes, GigaMUGA contains 2006 probes for copy number concentrated in structurally polymorphic regions of the mouse genome. The performance of the array is characterized in a set of 500 high-quality reference samples spanning laboratory inbred strains, recombinant inbred lines, outbred stocks, and wild-caught mice. GigaMUGA is highly informative across a wide range of genetically diverse samples, from laboratory substrains to other Mus species. In addition to describing the content and performance of the array, we provide detailed probe-level annotation and recommendations for quality control.